2009
DOI: 10.1249/mss.0b013e31819e02f2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamins, Amino Acids, and Renal Function in Postexercise Hyperhomocysteinemia

Abstract: Our results show that higher plasma concentrations of tHcy after an acute intense exercise are associated to higher concentrations of rHcy, and this effect is independent of the type of exercise, vitamin status, or amino acid metabolic stress but could be related to potential changes in the renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
2
33
0
4
Order By: Relevance
“…These authors suggested that the high intensity sustained by the runners comparing to the 100 km run and mountain bike race, can have more rest periods during trials, being a possible answer of this response. In contrast, other research studies including different intensities showed that the tHcy increase is independent of the intensity of the exercise [11,24] or type of exercise [22]. Sotgia et al [21], who compared athletes and non-athletes subjects, found no changes in tHcy after acute exercise but a decrease in the Homocysteine reduced form [21].…”
Section: Acute Effect Of Exercise On Thcy Concentrationsmentioning
confidence: 92%
“…These authors suggested that the high intensity sustained by the runners comparing to the 100 km run and mountain bike race, can have more rest periods during trials, being a possible answer of this response. In contrast, other research studies including different intensities showed that the tHcy increase is independent of the intensity of the exercise [11,24] or type of exercise [22]. Sotgia et al [21], who compared athletes and non-athletes subjects, found no changes in tHcy after acute exercise but a decrease in the Homocysteine reduced form [21].…”
Section: Acute Effect Of Exercise On Thcy Concentrationsmentioning
confidence: 92%
“…Increased plasma Hcy concentrations have been observed in several studies using different exercise intensities and modalities (Herrmann et al 2003a, b;König et al 2003;Real et al 2005;Venta et al 2009). However, Venta et al (2009) reported that the exact mechanism by which plasma Hcy concentrations increase after acute exercise is unknown. Also, the effects of creatine supplementation on Hcy levels after acute aerobic and anaerobic exercise are unknown.…”
Section: Introductionmentioning
confidence: 95%
“…The results of (17) showed that higher plasma concentrations of Hcy after acute exercise are independent of vitamin status, or amino acid metabolic stress but could be related to potential changes in renal function.…”
Section: Discussionmentioning
confidence: 98%